2011
DOI: 10.1074/jbc.m111.277087
|View full text |Cite
|
Sign up to set email alerts
|

Different Signaling Pathways Stimulate a Disintegrin and Metalloprotease-17 (ADAM17) in Neutrophils during Apoptosis and Activation

Abstract: Background: Neutrophil ADAM17 (a disintegrin and metalloprotease-17) mediates the proteolytic release of receptors and soluble factors that regulate inflammation. Results: ADAM17 stimulation during Fas-induced neutrophil apoptosis requires caspase-8, Bid, and mitochondrial reactive oxygen species. Conclusion: Neutrophil ADAM17 stimulation occurs by different signal transduction pathways during activation and apoptosis. Significance: ADAM17 activation in apoptotic neutrophils may rapidly down-regulate their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Nox4 involvement in ECM accumulation has been reported by several groups (2,6,8,22,38,44). Additionally, there is evidence that ROS activates ADAM17 (16,37,49). However, only one publication has shown upregulation of NADPH oxidases and subsequent ROS production, which results in shedding of known ADAM17 substrates (36).…”
Section: Discussionmentioning
confidence: 97%
“…Nox4 involvement in ECM accumulation has been reported by several groups (2,6,8,22,38,44). Additionally, there is evidence that ROS activates ADAM17 (16,37,49). However, only one publication has shown upregulation of NADPH oxidases and subsequent ROS production, which results in shedding of known ADAM17 substrates (36).…”
Section: Discussionmentioning
confidence: 97%
“…Cells were stained with antibodies against extracellular antigens and were then fixed and permeabilized before intracellular staining to detect IFN-g. A highly selective ADAM17 inhibitor (BMS566394) from Bristol-Myers Squibb (referred to as inhibitor 32) 23 was used at a 10 mM concentration, as previously described, 24 and was added to 1 3 10 6 /mL purified NK cells 30 minutes before testing. We also used a specific ADAM17 inhibitory monoclonal antibody (D1[A12], 6 mg/mL) generated by phage display that contains individual antibody variable domains to 2 distinct ADAM17-specific epitopes 25 to confirm ADAM17 specificity (kindly provided by Dr Gillian Murphy, University of Cambridge, UK).…”
Section: Cytokine Stimulationmentioning
confidence: 99%
“…It has been previously reported that MPTP opening induces mitochondria to produce large amounts of ROS [34][35][36][37][38]. Several reports have confirmed that ROS activate ADAM17 [39,40]. In order to demonstrate that A23187 induces mitochondria to produce ROS, we used MitoSOXÔ Red, an indicator of mitochondrial superoxide production, to detect mitochondrial ROS.…”
Section: A23187 Induces Elevation Of Mitochondrial Rosmentioning
confidence: 96%
“…It is known that the enhanced production of ROS is associated with ADAM17-mediated ectodomain shedding in various cells [40,43]. However, whether ROS are implicated in A23187induced GPIba ectodomain shedding remains unknown.…”
Section: A23187-induced Gpiba Ectodomain Shedding Is Partially Inhibimentioning
confidence: 99%